DESIGN AND CHARACTERIZATION OFBROADBAND SWITCH MODE CLASS E RADIO FREQUENCY POWER AMPLIFIER AT 3.4-3.6 GHZ BAND - Hamid Al-Azhari, Abdurrakhman
The growing telecommunications system has increased the use of electronic devices connected to the internet. 5G technology, which is increasingly developing, has